(untitled) (Regional aspects of productive forces development of Ukraine, 2023)
Introduction. In modern conditions, the economic development of Ukraine is connected with many factors, first of all, with the functioning of the labor market. It is characterized as a complex socio-economic phenomenon of society. Therefore, the study of the conceptual provisions of the paradigm of formation and regulation of the labor market is relevant and timely, given that their results will significantly affect the reproduction and development of labor resources of both enterprises, regions, and the state in general. The purpose of the article is a thorough analysis and systematization of scientific approaches to the creation of a modern paradigm of formation and regulation of the labor market. Research methods. During the writing of the scientific article, the historical method, methods of logical generalization, theoretical analysis and synthesis were applied. The results. Attention is focused on definitions of the concept of "labor market", taking into account that in modern economic literature there is no single interpretation of this concept, sometimes it is defined as "labor market". Different views of the authors on these concepts are due to the purpose of researching specific aspects of labor activity. The analysis of literary sources makes it possible to assert that for the first time the definition of the essence of the labor market was developed in the works of modern researchers who used the scientific results of A. Smith, D. Ricardo, D. S. Mill, K. Marx, A. Marshall, A. Pigou, L. Walrasom, V. Pareto, J. Keynes, P. Samuelson and others.The analysis of the evolution of scientific views on the essence of the concept of "labor market" makes it possible to determine the main stages of its formation and regulation in the context of ensuring the effectiveness and efficiency of labor activity in modern conditions. Conclusions. As a result of the generalization of scientific sources, domestic and foreign studies regarding the essence of the "labor market", it was established that there is no unified opinion regarding the definition of the meaning of this concept. This is explained by the complexity and multifaceted nature of the concept, which is in a state of transformation, associated with rapid changes. Defining the conceptual provisions of the paradigm of formation and regulation of the labor market will contribute to the development of economic theory and provide the essence of its conceptual apparatus.